Gout : the patrician malady / Roy Porter and G.S. Rousseau. - Porter, Roy, 1946- (Yale University Press, 2000)
Historically seen as a disease affecting upper-class males of superior wit and creativity, gout has fascinated medical writers and commentators from the time of ancient Greece. This book investigates the medical thinking about gout through the ages.